Municipal Solid Waste Management Practices and Opportunities in Saudi Arabia - Radwan, N.; Mangi, S. A. (Engineering, Technology & Applied Science Research, 2019)
Municipal solid waste management has been given serious attention by the authorities of Saudi Arabia (SA). This study focuses on municipal solid waste (MSW) that predominantly contains food, paper, and plastic waste. However, improper handling of MSW causes several environmental and human health issues. Therefore, it is necessary to review the current practices and future opportunities that have been adopted for solid waste collection, handling, and disposal. Considering the current scenario, this study proposed a reversal approach for MSW management. This study considered that MSW generated in SA has great potential to be converted into wealth. Hence, considering the hostile environment anaerobic treatment and incineration for MSW has been proposed in this study for future research.